Macrosystems ecology: understanding ecological patterns and processes at continental scales. Issue 1 (1st February 2014) - Heffernan, James B; Soranno, Patricia A; Angilletta, Michael J; Buckley, Lauren B; Gruner, Daniel S; Keitt, Tim H; Kellner, James R; Kominoski, John S; Rocha, Adrian V; Xiao, Jingfeng; Harms, Tamara K; Goring, Simon J; et al.
Abstract : Macrosystems ecology is the study of diverse ecological phenomena at the scale of regions to continents and their interactions with phenomena at other scales. This emerging subdiscipline addresses ecological questions and environmental problems at these broad scales. Here, we describe this new field, show how it relates to modern ecological study, and highlight opportunities that stem from taking a macrosystems perspective. We present a hierarchical framework for investigating macrosystems at any level of ecological organization and in relation to broader and finer scales. Building on well‐established theory and concepts from other subdisciplines of ecology, we identify feedbacks, linkages among distant regions, and interactions that cross scales of space and time as the most likely sources of unexpected and novel behaviors in macrosystems. We present three examples that highlight the importance of this multiscaled systems perspective for understanding the ecology of regions to continents.